2012
DOI: 10.1590/s1020-49892012000900004
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-related lower-extremity amputation incidence and risk factors: a prospective seven-year study in Costa Rica

Abstract: Those most likely to undergo LEA among Costa Rican diabetic patients were men with 10 or more years of diabetes and average HbA1c > 8% who used insulin and had diabetic retinopathy. Patients on insulin therapy were at greatest risk, especially those with a previous amputation. Diabetic patients with the above-mentioned profile should be considered to be at very high risk of LEA and followed closely by the health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 43 publications
(46 reference statements)
7
54
0
10
Order By: Relevance
“…Following the reading of the full text of the remaining 47 articles, 39 articles were excluded, including six reviews, 22 articles in which the data could not be extracted and 11 articles with duplicated populations. Finally, eight documents were included in this meta-analysis (23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the reading of the full text of the remaining 47 articles, 39 articles were excluded, including six reviews, 22 articles in which the data could not be extracted and 11 articles with duplicated populations. Finally, eight documents were included in this meta-analysis (23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Resultsmentioning
confidence: 99%
“…Table I indicates the basic information of the studies involved in the meta-analysis. The enrolled eight studies included five cohort studies (22)(23)(24)26,27) and three case control studies (20,21,25). The publication year ranged from 1992-2015.…”
Section: Resultsmentioning
confidence: 99%
“…20 In a study from Costa Rica showed that diabetic patients who had undergone LEA were men with 10 or more years of diabetes and average HbA1C more than 8%. 21 The number of female patients in our study was 26 (32.91%) out of a total number of 79 patients. Out of total number of 29 amputees, 7 were female patients (24.14%).…”
Section: Resultsmentioning
confidence: 75%
“…The diabetic retinopathy accounts for approximately 12% of blindness, and its development is closely related to the time and severity of hyperglycemia, which can develop on average seven years before the diagnosis of DM (1) . A prospective study, which has been conducted in Costa Rica, found that retinopathy was a risk factor for amputation in patients with DM, as well as the longer time of diagnosis, elevated glycated hemoglobin and insulin therapy (20) . Moreover, the visual deficit interferes in the individual's capacity for self-care, especially in this sample in which the majority of participants were elderly.…”
Section: Discussionmentioning
confidence: 99%